2009
DOI: 10.1371/journal.pone.0004848
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CWD Prions in Urine and Saliva of Deer by Transgenic Mouse Bioassay

Abstract: Chronic wasting disease (CWD) is a prion disease affecting captive and free-ranging cervids (e.g. deer, elk, and moose). The mechanisms of CWD transmission are poorly understood, though bodily fluids are thought to play an important role. Here we report the presence of infectious prions in the urine and saliva of deer with chronic wasting disease (CWD). Prion infectivity was detected by bioassay of concentrated, dialyzed urine and saliva in transgenic mice expressing the cervid PrP gene (Tg[CerPrP] mice). In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
200
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(206 citation statements)
references
References 36 publications
(47 reference statements)
6
200
0
Order By: Relevance
“…Indeed, deer with clinical CWD and mild to moderate nephritis produced urine containing sPMCA-detectable PrP Sc and CWD-infectivity. 41 Overall, data demonstrates the secretion of prion within the urine of animals in the terminal stages of prion disease at levels 10-fold lower 38 or similar to 37 that found in plasma; the latter estimated to be approximately 0.5-5 fg/ml of PrP Sc . 38 While not a prerequisite for prionuria, nephritis may well lead to the increased secretion of prion within urine.…”
Section: In Vivo Dissemination Of Prp Sc and Prion Infectivitymentioning
confidence: 79%
See 1 more Smart Citation
“…Indeed, deer with clinical CWD and mild to moderate nephritis produced urine containing sPMCA-detectable PrP Sc and CWD-infectivity. 41 Overall, data demonstrates the secretion of prion within the urine of animals in the terminal stages of prion disease at levels 10-fold lower 38 or similar to 37 that found in plasma; the latter estimated to be approximately 0.5-5 fg/ml of PrP Sc . 38 While not a prerequisite for prionuria, nephritis may well lead to the increased secretion of prion within urine.…”
Section: In Vivo Dissemination Of Prp Sc and Prion Infectivitymentioning
confidence: 79%
“…70 The amounts of prion present in saliva are likely to be low as indicated by CWD-infected saliva producing prolonged incubation periods and incomplete attack rates within the transgenic mouse bioassay. 41 …”
Section: Secretion Of Prions Within Milkmentioning
confidence: 99%
“…79,80 The vehicle responsible for the spread of prions between cage-mates is uncertain, but other studies in cervids and rodent model systems support the plausibility of biological fluids and excreta as transmission vehicles. 48,81,82 Given the presence of PrP RES in the taste buds of inoculated Tg[CerPrP] mice, horizontal spread could be linked to the shedding of prion-infected cells into oronasal secretions. 71 In addition to direct animal-to-animal contact or animal-to-excreta contact, coprophagy is also plausible, as evidenced by the transmission of CWD and scrapie by exposure of naive animals to a contaminated environment.…”
Section: Discussionmentioning
confidence: 99%
“…Blood, saliva, urine and faeces of infected animals are potential sources of CWD infection within a herd (Sigurdson et al, 1999;Mathiason et al, 2006;Haley et al, 2009;Tamgüney et al, 2009). Additional laboratory evidence demonstrated that both skeletal muscle and central nervous system tissues are important sources of prions that can result in CWD (Angers et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Prions in urine, faecal material or from an infected carcass can enter the environment and remain infectious for long periods Haley et al, 2009;Saunders et al, 2012). Prions bind strongly to various types of soil and resist removal by water or various solvents (Leita et al, 2006;Saunders et al, 2008) so though possibly long-lasting, there is little subsequent migration or leaching through the soil (Jacobson et al, 2010;Maddison et al, 2010).…”
Section: Introductionmentioning
confidence: 99%